Nickel-cobalt nanosheet electrocatalyst for in-situ growth and preparation method and application of nickel-cobalt nanosheet electrocatalyst

Through the in-situ electrocatalyst, the defect of using precious metal catalysts in the existing electrochemical oxidation process of ethylene glycol is solved, and efficient and low-cost oxidation of ethylene glycol is achieved, forming formate salts, and improving economic value.

CN119592995AActive Publication Date: 2025-03-11TONGJI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411884350.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The catalysts used in the existing electrochemical oxidation process are mainly precious metals, such as palladium, platinum, and gold. It is of great significance to develop highly active non-precious metal electrocatalysts.

Method used

In situ grown nickel-cobalt nanosheet array electrocatalyst is used to soak the foam metal in a mixture of nickel and cobalt salts to achieve in situ growth of nickel-cobalt nanosheets and the formation of array structure.

Benefits of technology

The catalyst can efficiently oxidize ethylene glycol under alkaline conditions to generate high-value formate, which improves economic value, while avoiding the use of precious metals and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592995A_ABST
    Figure CN119592995A_ABST
Patent Text Reader

Abstract

The invention relates to an in-situ growth nickel-cobalt nanosheet electrocatalyst and a preparation method and application thereof.Foam metal is soaked in a mixed solution of nickel salt and cobalt salt, the nickel-cobalt nanosheet array electrocatalyst growing on the foam metal in situ is obtained through reaction, and metal more active than cobalt and nickel is selected as the foam metal. Compared with the prior art, the in-situ growth strategy avoids the use of an adhesive, and the prepared nickel-cobalt nanosheet array structure which grows on the foam iron in situ and is regularly arranged is beneficial to accelerating diffusion mass transfer of a catalytic reaction and accelerating rapid desorption of accumulated bubbles and has a large specific surface area; therefore, active sites are fully exposed, the reaction kinetics is improved, and the catalytic activity and stability can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to an in-situ grown nickel-cobalt nanosheet electrocatalyst and a preparation method and application thereof. Background Art

[0002] Plastics are widely used in human society because of their cheapness and versatility. Plastics are difficult to decompose and cause great pollution to the environment. Polyethylene terephthalate (PET) is the most widely used polyester plastic with its excellent performance and diverse applications. The annual output exceeds 70 million tons, but only 20% of PET is recycled, and most of it is discarded, causing environmental pollution. In the past few decades, some chemical methods for PET recycling, such as hydrolysis and alcoholysis, have been reported one after another. Relevant studies have found that PET can be completely hydrolyzed into terephthalic acid and ethylene glycol in an alkaline environment. Terephthalic acid is recovered from the hydrolyzate through processes such as acidification and recrystallization, which is conducive to reducing pollution and increasing economic value. However, ethylene glycol is difficult to separate due to its high boiling point (197.3℃) and good water solubility. It is very meaningful to explore methods for separating or converting ethylene glycol from the hydrolyzate.

[0003] Electrochemical oxidation of ethylene glycol is a new idea for separation and conversion. Renewable electricity drives the oxidation of ethylene glycol in PET hydrolysate into high-value chemicals, which increases the economic value. Ethylene glycol is easier to oxidize than water. Ethylene glycol can be selectively oxidized to glycolic acid or formic acid. Among them, formic acid or formates are widely used in the pharmaceutical, feed and leather industries. Ethylene glycol oxidation (EGOR) is considered to be a clean and economically effective value-added chemical process. However, the current electrochemical oxidation of ethylene glycol process often uses precious metal catalysts such as palladium, platinum, and gold. It is very meaningful to develop highly active non-precious metal electrocatalysts. Summary of the invention

[0004] The purpose of the present invention is to overcome the defect that the catalyst currently used in the electrochemical oxidation of ethylene glycol is a precious metal catalyst, thereby providing an in-situ grown nickel-cobalt nanosheet electrocatalyst and its preparation method and application.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] The technical solution of the present invention is to provide a method for preparing an in-situ grown nickel-cobalt nanosheet electrocatalyst: immersing a foam metal in a mixed solution of a nickel salt and a cobalt salt, and reacting to obtain a nickel-cobalt nanosheet array electrocatalyst in-situ grown on the foam metal, wherein the foam metal is a metal that is more active than cobalt and nickel.

[0007] In some specific embodiments, the nickel salt is selected from any one of nickel sulfate, nickel sulfate hexahydrate, nickel chloride, and nickel nitrate.

[0008] In some specific embodiments, the cobalt salt is selected from any one of cobalt sulfate, cobalt sulfate heptahydrate, cobalt chloride, and cobalt nitrate.

[0009] In some specific embodiments, the total concentration of nickel salt and cobalt salt in the mixed solution is 50 mM, and the molar ratio of nickel salt to cobalt salt is 3 / 7 to 7 / 3.

[0010] In some specific embodiments, the molar ratio of the nickel salt to the cobalt salt is 7:3, 1:1, or 3:7.

[0011] In some specific embodiments, the metal foam is iron foam (IF).

[0012] In some specific embodiments, the reaction temperature is room temperature, and the reaction time is (1.5-2.5) h.

[0013] In some specific embodiments, the preparation method further comprises: performing CV oxidation on the nickel-cobalt nanosheet array electrocatalyst grown in situ on the foam metal, specifically:

[0014] A mercury / mercury oxide electrode was used as a reference electrode, a platinum sheet was used as a counter electrode, and a nickel-cobalt nanosheet array electrocatalyst in situ grown on metal foam was used as a working electrode. They were placed in 1 M KOH and subjected to CV treatment at a scan rate of 10 mV / s at 0.146 V-0.946 V to obtain nickel-cobalt oxide covered on the metal foam.

[0015] CV oxidation oxidizes nickel and cobalt into nickel oxide and cobalt oxide, which cover the surface of the foam metal to prevent it from rusting.

[0016] The second technical solution of the present invention is to provide an in-situ grown nickel-cobalt nanosheet array electrocatalyst, which is obtained based on the method described in one of the above technical solutions.

[0017] The third technical solution of the present invention is to provide an application of an in-situ grown nickel-cobalt nanosheet array electrocatalyst as described in one of the above technical solutions, wherein the in-situ grown nickel-cobalt nanosheet array electrocatalyst is used to process ethylene glycol and plastics into value-added chemicals.

[0018] In some specific embodiments, under alkaline conditions, the in-situ grown nickel-cobalt nanosheet array electrocatalyst catalyzes the oxidation of ethylene glycol and PET hydrolysis products to generate formate.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The in-situ growth strategy of the present invention avoids the use of adhesives, ensures close contact between the cobalt-nickel nanosheet array electrocatalyst and the foam metal conductive substrate interface, and promotes rapid charge transfer. Cobalt doping can promote charge transfer and regulate Ni 2+ / Ni 3+ The position of the redox couple is adjusted, thereby effectively improving the catalytic activity.

[0021] (2) The iron in the foamed iron is more active than cobalt and nickel and can be used for electrochemical replacement reactions. The regularly arranged nickel-cobalt nanosheet array structure grown in situ on the foamed iron is beneficial to accelerating the diffusion mass transfer of the catalytic reaction, accelerating the rapid desorption of accumulated bubbles, and having a large specific surface area, thereby fully exposing the active sites, improving the reaction kinetics, and effectively improving the catalytic activity and stability.

[0022] (3) The preparation method of the present invention is low-cost, easy to operate, has zero energy consumption, and is scalable. The prepared product has good ethylene glycol oxidation (EGOR) electrocatalytic activity in alkaline electrolyte, and can achieve the production of value-added chemical formate at a relatively low voltage input. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 For you 0.3 Co 0.7 / IF scanning electron microscopy (SEM) (A, B) and transmission electron microscopy (TEM) (C).

[0024] Figure 2 A~D are scanning electron microscope images of NiCo / IF with different nickel-cobalt ratios.

[0025] Figure 3 For you 0.3 Co 0.7 Elemental distribution map of / IF catalyst.

[0026] Figure 4 Linear sweep voltammetry curves of catalysts with different nickel-cobalt ratios in ethylene glycol oxidation (A) and Ni 0.3 Co 0.7 EGOR stability diagram of / IF electrode (B).

[0027] Figure 5 For you 0.3 Co 0.7 / H-NMR spectrum (A) and C-NMR spectrum (B) of the electrolysis products of ethylene glycol by IF electrocatalysis.

[0028] Figure 6 The reaction pathway for the oxidation of ethylene glycol to formate in alkaline medium.

[0029] Figure 7This is a graph of the Tafel slope values ​​of catalysts with different nickel-cobalt ratios.

[0030] Figure 8 Electrochemical impedance spectroscopy of catalysts with different nickel-cobalt ratios.

[0031] Fig. 9 is the double-layer capacitance of catalysts with different nickel-cobalt ratios.

[0032] Fig.10 A standard curve of formic acid was prepared for liquid phase calibration.

[0033] Fig.11 Linear sweep voltammetry curves of catalysts with different nickel-cobalt ratios in PET plastic hydrolysis solution (A), nuclear magnetic hydrogen spectrum of electrolysis products (B), and cyclic voltammetry curves of catalysts with different nickel-cobalt ratios in blank alkaline solution (C). DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0035] In the following examples and comparative examples, cobalt sulfate heptahydrate, nickel sulfate hexahydrate, and ethylene glycol were purchased from Shanghai McLean Biochemical Technology Co., Ltd., and electrochemical data were collected by CHI760E (Shanghai Chenhua). The remaining raw materials, products, or processing technologies not specifically described are indicated to be conventional commercially available products or conventional processing technologies in the art.

[0036] Embodiment 1:

[0037] Weigh 0.263 g of nickel sulfate hexahydrate and 0.281 g of cobalt sulfate heptahydrate and dissolve them in 20 mL of deionized water to form a uniform mixed solution. Add the solution to a beaker containing clean foam iron. After 2 h of reaction at room temperature, a nickel-cobalt nanosheet array supported on the foam iron can be obtained, which is recorded as Ni 0.5 Co 0.5 / IF, place in a vacuum drying oven at 80℃ for later use.

[0038] Embodiment 2:

[0039] Compared with Example 1, most of the above are the same, except that the total concentration of nickel sulfate hexahydrate and cobalt sulfate heptahydrate is controlled to be 50 mM, and the molar ratio of nickel sulfate hexahydrate to cobalt sulfate heptahydrate is adjusted to 3:7, so as to prepare a nickel-cobalt nanosheet array supported on foamed iron, which is denoted as Ni 0.3 Co 0.7 / IF.

[0040] Embodiment 3:

[0041] Compared with Example 1, most of the above are the same, except that the total concentration of nickel sulfate hexahydrate and cobalt sulfate heptahydrate is controlled to be 50 mM, and the molar ratio of nickel sulfate hexahydrate to cobalt sulfate heptahydrate is adjusted to 7:3, so as to prepare a nickel-cobalt nanosheet array supported on foamed iron, which is denoted as Ni 0.7 Co 0.3 / IF.

[0042] Embodiment 4:

[0043] Based on the Ni obtained in Example 1 0.5 Co 0.5 / IF.

[0044] Since the replaced metal elements Ni and Co will form micro-galvanic cells with the foam iron substrate, accelerating the rusting of the foam iron surface. 0.5 Co 0.5 / IF performs CV oxidation, specifically:

[0045] Mercury / mercury oxide electrode was used as reference electrode, platinum sheet as counter electrode, Ni 0.5 Co 0.5 / IF was used as the working electrode, placed in 1M KOH, and subjected to CV treatment at 0.146V-0.946V at a scan rate of 10mV / s to obtain nickel cobalt oxide covered on the foamed iron, which was recorded as NiCoOx / IF.

[0046] Comparative Example 1:

[0047] Compared with Example 1, most of the contents are the same, except that the cobalt sulfate heptahydrate is replaced with an equal molar amount of nickel sulfate hexahydrate to prepare a nickel nanosheet array supported on foamed iron, which is denoted as NiFe.

[0048] Comparative Example 2:

[0049] Compared with Example 1, most of the contents are the same, except that nickel sulfate hexahydrate is replaced with cobalt sulfate heptahydrate in an equal molar amount to prepare a cobalt nanosheet array supported on foamed iron, which is denoted as CoFe.

[0050] Figure 1 Shows Ni 0.3 Co 0.7 / IF scanning electron microscope and transmission electron microscope images, from which we can see that nickel and cobalt are evenly loaded on the surface of foamed iron. 0.3 Co 0.7 / IF exhibits a two-dimensional flake-like morphology and a smooth surface.

[0051] Figure 2The scanning electron microscope images of NiCo / IF with different nickel-cobalt ratios are shown, and it can be seen that they all present a nanosheet array structure.

[0052] Figure 3 For you 0.3 Co 0.7 The element distribution diagram of / IF shows that the product is mainly composed of three elements: Ni, Co and Fe.

[0053] The prepared Ni 0.3 Co 0.7 / IF catalyst as a catalyst for ethylene glycol oxidation or PET hydrolysis product oxidation:

[0054] At room temperature, the reaction system is a three-electrode system, Ni 0.3 Co 0.7 / IF catalyst was used as working electrode, graphite rod was used as counter electrode, and mercury / mercuric oxide was used as reference electrode.

[0055] (1) The OER test was carried out in 1.0 M KOH solution.

[0056] (2) EGOR test was carried out in 1.0 M KOH solution or PET hydrolyzate containing 0.5 M EG (ethylene glycol).

[0057] The preparation method of PET hydrolyzate refers to the following steps:

[0058] 5.6 g of dried PET powder was added to 50 mL of 2 M KOH solution and transferred to a 100 mL Teflon-lined autoclave, which was sealed and kept at 160 °C for 4 h. After cooling to room temperature, the filtered solution containing ethylene glycol and terephthalic acid was used as the electrolyte for electrochemical testing and analysis.

[0059] (3) The scanning rate of cyclic voltammetry and linear sweep voltammetry was 5 mV s -1 .

[0060] (4) Electrochemical impedance spectroscopy (EIS) measurements were performed in the frequency range of 1 MHz to 0.01 Hz with an amplitude of 5 mV.

[0061] (5) The Tafel slope is obtained from the LSV plot using a linear fit applied to the points in the Tafel region.

[0062] (6) The double-layer capacitance (Cdl) was calculated by CV in the potential range of 0.824 V to 0.924 V (vs. RHE) at different scan rates.

[0063] (7) The catalyst stability was evaluated by constant current chronopotentiometry.

[0064] (8) Detection method of electrolysis products:

[0065] After the electrolysis, the electrolyte solution was collected and quantitatively tested by liquid chromatography (HPLC). For each HPLC measurement, 50 μL of the electrolyte solution containing the product was washed with dilute H 2 SO 4 The solution was diluted to 1 mL, and then 20 μL of the prepared sample was injected into the BioRad Aminex 87H column. 5 mM H 2 SO 4 The solution was used as the mobile phase at a constant flow rate of 0.6 mL / min. The product class was determined by comparing the retention time of the eluted peak with that of a single standard sample solution.

[0066] The results are as follows:

[0067] (1) Evaluation of EGOR performance of electrocatalysts with different nickel-cobalt ratios:

[0068] Figure 4 Figure A shows the linear sweep voltammetric curves of EGOR of different catalysts. It can be seen that Ni 0.3 Co 0.7 / IF catalysts exhibit lower initial oxidation potential and higher catalytic activity. Figure 4 B indicates Ni 0.3 Co 0.7 / IF catalyst has good ethylene glycol oxidation stability.

[0069] Figure 5 Figure A is Ni 0.3 Co 0.7 The H NMR spectrum of the product collected after long-term electrolysis of ethylene glycol by / IF catalyst. The blue and green shadows represent the positions of the characteristic peaks of H NMR spectrum of ethylene glycol and formate, respectively. It can be seen that after long-term electrolysis, the peak of ethylene glycol disappears, and a strong peak of formate appears at 8.4ppm, indicating that ethylene glycol is effectively converted into formate. Figure 5 B is the carbon NMR spectrum. It can be seen that after a long period of electrolysis, the peak of ethylene glycol disappears and a strong formate peak appears.

[0070] Figure 6 The following is a possible reaction pathway for the oxidation of ethylene glycol to formate in an alkaline medium. First, the formation of formic acid begins with the oxidation of ethylene glycol to glycolaldehyde with the breaking of the CC bond. Subsequently, glycolaldehyde is oxidized and cleaved to generate formic acid and formaldehyde, and then methanol and formic acid are generated through the intermolecular redox reaction of formaldehyde in an alkaline solution (Cannizzaro reaction), and finally methanol is oxidized to formic acid.

[0071] Figure 7 , 8, 9 are the Tafel slope value, electrochemical impedance spectrum and double layer capacitance of the catalysts with different nickel-cobalt ratios, respectively.

[0072] (2) Performance evaluation of electrocatalysts with different nickel-cobalt ratios for PET:

[0073] Polyethylene terephthalate (PET) can be hydrolyzed in alkaline solution to obtain monomers such as terephthalic acid (PTA) and ethylene glycol (EG). Converting the ethylene glycol component in PET plastic into high-value-added formate by electrocatalysis is a green, environmentally friendly, and economically sustainable method, which greatly improves the profitability of waste PET recycling.

[0074] The amount of formic acid Fig.10 Prepare a series of formic acid standard solutions, and mix 50 μL of formic acid standard solution with dilute H 2 SO 4 The solution was diluted to 1 mL, and then 20 μL of the prepared sample was injected into the BioRad Aminex 87H column. 5 mM H 2 SO 4 The solution was used as the mobile phase at a constant flow rate of 0.6 mL / min. A standard curve was prepared by calculating the peak area of ​​the elution peak.

[0075] Fig.11 A shows the polarization curves of PET hydrolyzate catalyzed by electrocatalysts with different Ni / Co ratios. The PET hydrolyzate was used as the electrolyte, which showed very similar EGOR performance to OER (ref. Fig.11 C), EGOR has lower initial oxidation potential and catalytic activity. Fig.11 B shows the electrochemical oxidation products of PET plastic hydrolysate 1 H NMR results, blue, yellow, and green shadows represent the positions of the characteristic peaks of ethylene glycol, terephthalate, and formate, respectively. It can be seen that after complete electrolysis, the peak of ethylene glycol disappears and the characteristic peak of formate appears, indicating that the PET hydrolyzate is effectively converted into value-added formate and terephthalate in the electrolyte. Therefore, the electrocatalytic reforming strategy of upgrading and recycling waste PET plastics into high-value-added formate chemicals using the catalyst prepared by the present invention is feasible.

[0076] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an in-situ grown nickel-cobalt nanosheet electrocatalyst, characterized in that: The foamed metal is immersed in a mixture of nickel salt and cobalt salt to react and obtain a nickel-cobalt nanosheet array electrocatalyst in situ grown on the foamed metal, wherein the foamed metal is a metal that is more active than cobalt and nickel.

2. The preparation method according to claim 1, characterized in that: The nickel salt is selected from any one of nickel sulfate, nickel sulfate hexahydrate, nickel chloride and nickel nitrate.

3. The preparation method according to claim 1, characterized in that: The cobalt salt is selected from any one of cobalt sulfate, cobalt sulfate heptahydrate, cobalt chloride and cobalt nitrate.

4. The preparation method according to claim 1, characterized in that: The total concentration of nickel salt and cobalt salt in the mixed solution is 50 mM, and the molar ratio of nickel salt to cobalt salt is 3 / 7 to 7 / 3.

5. The preparation method according to claim 1, characterized in that: The foam metal is foam iron.

6. The preparation method according to claim 1, characterized in that: The reaction temperature is room temperature, and the reaction time is (1.5-2.5) h.

7. The preparation method according to claim 1, characterized in that: The preparation method further comprises: performing CV oxidation on the nickel-cobalt nanosheet array electrocatalyst grown in situ on the foam metal, specifically: A mercury / mercury oxide electrode was used as a reference electrode, a platinum sheet was used as a counter electrode, and a nickel-cobalt nanosheet array electrocatalyst in situ grown on metal foam was used as a working electrode. They were placed in 1 M KOH and subjected to CV treatment at a scan rate of 10 mV / s at 0.146 V-0.946 V to obtain nickel-cobalt oxide covered on the metal foam.

8. An in-situ grown nickel-cobalt nanosheet array electrocatalyst, characterized in that: Obtained based on the preparation method according to any one of claims 1 to 7.

9. An application of the in-situ grown nickel-cobalt nanosheet array electrocatalyst as claimed in claim 8, characterized in that: The in situ grown nickel-cobalt nanosheet array electrocatalyst is used to process ethylene glycol and plastics into value-added chemicals.

10. The use according to claim 9, characterized in that: The in-situ grown nickel-cobalt nanosheet array electrocatalyst catalyzes the oxidation of ethylene glycol and PET plastic hydrolysis products to generate formate.

Citation Information

Patent Citations

  • An oxygen evolution reaction electrode catalyst assembly comprising dendritic nickel foam, its use and a method to produce said assembly

    CA3234979A1

  • Preparation method of non-noble metal NiCoFe / NF electrocatalyst and application of electrocatalyst to oxygen evolution

    CN110280249A

  • Two-dimensional conductive metallic organic compound array, preparation method and application

    CN110586190A

  • Method for synthesizing cobalt-doped ferronickel mesh nanosheet array efficient bifunctional electrocatalyst and application

    CN111437819A

  • Difunctional electrocatalyst with heterostructure nickel cobalt nitride nanosheet array and preparation and application of difunctional electrocatalyst

    CN114351185A